2003
DOI: 10.1046/j.1442-9993.2003.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant cover on seed removal by rodents in the Monte Desert (Mendoza, Argentina)

Abstract: In desert areas, predation risk is one of the highest costs of foraging and is a major influence on animal behaviour. Several strategies are used by foragers for surviving and reproducing in desert areas. The foraging strategies of the small mammals of South American deserts are still poorly known. In this study, we investigated the foraging strategies of rodents of the Monte Desert in response to distance from seed sources to sheltered sites (i.e. shrubs) during two different seasons (wet and dry). We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 34 publications
(68 reference statements)
1
39
0
Order By: Relevance
“…Another antipredator behavior is the mode of locomotion employed by rodents, which plays a vital role in determining their ability to elude predators (Thompson 1985;Djawdan and Garland 1988;Taraborelli et al 2003a). The structural complexity of the habitat may affect movement behavior by: (1) physically impeding locomotion (Schooley et al 1996), (2) making movement more conspicuous and thus riskier (Brillhart and Kaufman 1991;Borruel et al unpublished data), (3) providing a higher density of resources, hence favoring lower speeds so that resource opportunities are not missed (Brownsmith 1977), (4) increasing protection against predators through hiding cover (Thompson 1982;Taraborelli et al 2003b), (5) increasing visual obstruction, thus reducing the ability to detect predators (Schooley et al 1996;Ebensperger and Hurtado 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another antipredator behavior is the mode of locomotion employed by rodents, which plays a vital role in determining their ability to elude predators (Thompson 1985;Djawdan and Garland 1988;Taraborelli et al 2003a). The structural complexity of the habitat may affect movement behavior by: (1) physically impeding locomotion (Schooley et al 1996), (2) making movement more conspicuous and thus riskier (Brillhart and Kaufman 1991;Borruel et al unpublished data), (3) providing a higher density of resources, hence favoring lower speeds so that resource opportunities are not missed (Brownsmith 1977), (4) increasing protection against predators through hiding cover (Thompson 1982;Taraborelli et al 2003b), (5) increasing visual obstruction, thus reducing the ability to detect predators (Schooley et al 1996;Ebensperger and Hurtado 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Food abundance (Alm et al, 2002), seed size (Garb et al, 2000;Ivan and Swihart, 2000), hardness of seed hull (Sako et al, 2002), perishability (Post and Reichman, 1991;Hadj-Chikh et al, 1996), palatability or nutrient composition (Laska et al, 2003), secondary compounds (Dixon and Johnson, 1997), seed energetic value (Lewis et al, 2001) are important factors in influencing seed predation and hoarding by rodents. Body size, age, sex, social structure, food preference and predator avoidance of rodents (Kitchen et al, 1999;Arjo et al, 2002;Taraborelli et al, 2003;Vander Wall and Jenkins, 2003) are also important factors in influencing seed predation and hoarding by rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few caches were present in areas devoid of shrub skeletons. Taraborelli et al (2003) similarly found that Argentine desert rodents cached more seeds near sheltered versus unsheltered sites. Shrub cover was scarce in the burn area over hundreds of hectares for the first 13 months after the fire.…”
Section: Seed Fatesmentioning
confidence: 85%